Articulatory characterisation of Singapore Mandarin tones using ultrasound - Poh, Zhi Yun (Nanyang Technological University, 2024)
Unlike other varieties of Mandarin such as those spoken in Beijing or Taiwan, there have been limited acoustic studies on Singapore Mandarin tones. Despite this gap, existing studies indicate that Singapore Mandarin tones exhibit distinctive characteristics compared to other varieties. Tone production involves complex physiological processes, notably the vertical movement of the larynx which controls fo. However, the specific mechanisms underlying tone production in Singapore Mandarin have not been thoroughly investigated. The present study bridges this research gap by examining the production of the four Mandarin lexical tones in 42 native speakers of Singapore Mandarin. Laryngeal ultrasound was used to track laryngeal movement and the resulting data were analysed using optical flow analysis. Findings revealed intriguing patterns in the relationship between larynx height and fo for certain tones. Larynx height and fo did not directly correspond to each other, suggesting that there are other laryngeal mechanisms at play in pitch modulation. This lack of direct correspondence could potentially be attributed to a novel phenomenon, termed laryngeal medialisation, which emerged as a novel finding in Singapore Mandarin. The study found an association of increased medialisation in the production of low fo, which aligned with the findings of prior studies. However, there were patterns of laryngeal behaviour that required further physiological explanations, suggesting that the relationship between laryngeal medialisation and fo modulation in citation tones may be more complex than initially anticipated.